Analysis of Educators’ Work Motivation in Supporting Main Tasks of Development and Education Command of Indonesian Navy (Causal Study in Educators Group Kobangdikal, Surabaya) - Heribertus Yudho Warsono; Budiyanto Budiyanto; Akhmad Riduwan (AIBPM Publisher, 2019)
Indonesia is the biggest archipelagic state with at least 17.506 islands, the two-thirds of the area (70%) consists of sea waters with a coastline of 81,000 km and is located between two continents, namely Australia and Asia, and is located between two oceans, the Pacific and the Indian. Through the UN Assembly in Montego Bay about the International Law of the Sea, the principles of the principle of the archipelagic state are included in the UNCLOS 1982 (United Nations Convention on the Law of the Sea) which influences the use of the EEZ for the benefit of national welfare and development. According to Law no. 34 of 2004 concerning the TNI, article 9, the task of the Indonesian Navy is to prepare and foster the power to uphold the sovereignty and integrity of the NKRI and protect national interests in the sea of national jurisdiction. Escorting the sea to such an extent is a heavy duty for the Navy, with such a daunting task, compared to the very limited number of naval organization of the Navy, it requires professional and qualified Navy soldiers who are able to work well, to achieve the objectives of the Indonesian Navy as mandated by law. The Navy in carrying out its role as a national defense force in the sea needs to build, shape and improve the quality of its human resources, this is done in an effort to obtain the ability and appearance of professional Navy soldiers shown by their performance, based on the soul of Sapta Marga, Sumpah Praskar and the Indonesian Navy's Trisila, in an integrated, continuous and balanced manner with provision of skills through education and assignments. The Development and Education Command of the Navy (Kobangdikal) is one of the Navy's educational institutions which is the Main Command of the Development of the Navy and is directly under the Chief of Staff by having the main task of carrying out the formal Navy and non-formal education needed to improve Navy soldiers, carry out the study and development of the doctrine of marine operations and the doctrine of amphibious operations at the level of tactics as well as the study and development of general support for sea operations and tactical amphibious operations.2 In order to organize the formal education of the Navy, Kobangdikal was carrying out first education (Dikma), formation education (Diktuk), general development education (Dikbangum), specialization development education (Dikbangspes), science and technology education (Dikiptek), transitional education (Dikalih) and education needed in order to improve the quality of Navy personnel. The Navy's educational philosophy, namely